Handbook of gear design - Maitra, Gitin M. (McGraw-Hill, 1994)
This book provides extensive information on various aspects of gears and gearing systems. It contains enough tables, illustrative examples and diagrams. It is based on ISO specifications and is a unique blend of practical as well as theoretical aspects of gear designs. It also includes more on spiral bevel gears, arcoid gears, klingelnberg and gleason systems and gear tooth checking